Fungal endocarditis in neonate - Verma, Manoj Kumar; Bharti, Abnish Kumar; Jaiswal, Rahul; Gupta, Amit; Gupta, Anuj (International Journal of Contemporary Pediatrics, 2020)
Neonatal endocarditis is a rare but usually fatal disease. Fungal endocarditis is an uncommon complication of invasive fungal infections and is associated with a high burden of morbidity and mortality. It frequently occurs in premature infants. The majority of these infections are caused by Candida (60-70%) and Aspergillus species (20-25%). The diagnosis is difficult because the criteria that have suggested and used in adults are not readily applicable for neonates. The incidence of fungal endocarditis in a neonate is on the rise, reported in the last decade secondary to use of central venous lines, frequent use of broad-spectrum antibiotics and neonatal surgical interventions.